THE RELATIONSHIP BETWEEN THE HABIT OF BRINGING LUNCH AND ENERGY INTAKE WITH NUTRITIONAL STATUS IN ADOLESCENT GIRLS AT SMAN 1 CIKARANG SELATAN: THE RELATIONSHIP BETWEEN THE HABIT OF BRINGING LUNCH AND ENERGY INTAKE WITH NUTRITIONAL STATUS IN ADOLESCENT GIRLS AT SMAN 1 CIKARANG SELATAN - Ramdayani, Zaskia; Rahmadina, Defa; Asmi, Nur Fauzia (STIKes Mitra Keluarga, 2024)
Introduction: School age is a critical stage where energy and nutrient needs must be met, as adolescents are in a phase of growth and development. Therefore, it is essential to ensure high-quality food that can meet the nutritional needs of adolescents while they are at school. The aim of this study is to determine the relationship between the habit of bringing lunch and energy intake with the nutritional status of female adolescents. Methods: This study used a quantitative approach with a cross-sectional design. The population in this study were adolescent female students at SMAN 1 Cikarang Selatan. The sample of 50 people was taken by purposive sampling. Data collection was conducted using a food consumption assessment questionnaire, namely the 24-hour food recall, along with a body weight scale, microtoise, and metline. Kolmogorov Smirnov test was used to test normality, and Pearson test to see the relationship between variables. Results: Based on statistical tests there is a relationship between the habit of bringing lunch with a significant nutritional status based on Z-Score IMT / U (p-value = 0.002), there is a relationship between the habit of bringing lunch withnutritional status based on %LILA (p-value 0.000) and there is no relationship between energy intake with nutritional status based on ZScore IMT/U (p-value 0.442), and no association was found between energy intake and nutritional status based on %LILA (p-value=0.570). Conclusion: There is a significant relationship between the habit of bringing lunch according to Z-Score IMT/U and %LILA.